Discussion of Fundamentalism Issue in “Fitna” The Movie Using Recontextualization Theory - Taufik Febriansyah (2008)
Fitna the movie is the way of Wilders to argue that Islam is a cruel religion and Islamisation must be stopped. Indeed there must be critics and opinions about the movie. This study is intended to find out the existence of recontextualization strategies of Indonesian people to construct the portrayal of Islam and examine how the audience’s perceive and responds Islamisation and fundamental issue. In analyzing the data the writer applies a CDA (Critical Discourse Analysis) framework proposed by Norman Fairclough using the theory of Recontextualization. In his analysis, the writer finds some strategies used by the audiences to recontextualize the discourse contained in the movie. The audiences think that the images of Islam depicted in the movie are very different than the description of Islam that they believe in. They think that Islam is a peaceful religion because as they know and learn it, Islam always teaches compassion and peacefulness. Depart from this way of thinking, the audiences recontextualize Islamisation as a process that should be done without any kind of forcing and violence. Another fact that the writer’s found is according to the Indonesian’s audience, Fitna is a documentary movie with no valid sources; that the credibility of the source is doubted because they sense that there is some kind of data manipulation intentionally presented to disrepute Islam. They consider that Wilders made the movie based on the wrong knowledge about Islam.